EFL STUDENTS’ PERCEPTIONS ON SUPPORTED SCHEMATA TOWARDS TRANSLATING VARIED TEXT USING GOOGLE TRANSLATE - M. Kharisma Nata A.; Rina Herlina; Wawan Tarwana (Universitas Galuh, 2022)
This study reports the analysis of students’ perception of using schemata towards Google Translate results and their strategies to use their schemata in improving Google Translate results. The approach of this research was a case study. Observation and interviews were used as the instrument for collecting the data. The subject of this study was students of grade three in the English Education Program at one private University in Ciamis and the data collection was derived from online class observation and interviews with translating lecturers. The results showed that the use of schemata is needed in translating text from Google Translate. The results also showed that the outline of students’ strategies to improve Google Translate results can be conducted by checking vocabulary, and sentence structure, and using their understanding or schemata. The researcher suggested for the students of the English Education Program practice translating more and keep expanding their views to make the quality of their translation even more perfect.